Expectations of the Participants of the Crop Insurance System and Their Implementation - Martynas Rusteika; Lina Skinulienė (Agriculture, 2023)
The manufacture of agriculture production products is the most sensitive to meteorological conditions. The main risks caused by adverse climate factors that Lithuania’s farmers confront are winterkill, hail, storms, and droughts. The aim of the study is to analyze the expectations of crop insurance system participants and to reveal the reasons for encouraging/discouraging farms in insuring their crops in Lithuania. All additional means (optimization of crop structure, changes in growing technologies) reduce the reliable harm of extreme climate change, but only technical, organizational means (crop insurance) can mostly reduce the loss of production. The investigation was underway using the analysis of scientific literature. Crop producers’ expectations of risk mitigation are influenced by a variety of factors: age, farm size, farming duration, locality, and farming practice. Farmers assess the government’s given support by way of compensation insurance fees. Farmers analyze the risk of the meteorological phenomenon and indicate that the farm would have huge damage from adverse climate conditions. The main obstacles to crop insurance are these: the farmers are too small for the insurance system; they want to separate risks insurance and to attain more possibilities to choose from; accent development of evaluation and payment of harms after agreeing that the evaluation is objective.